HER2-low expression in patients with hormone receptor positive and HER2 negative advanced breast cancer treated with ribociclib or palbociclib in combination with endocrine therapy - Kahraman, Seda; Hizal, Mutlu; Gumusay, Ozge; Basaran, Gul; Seyyar, Mustafa; Sahin, Elif; Sendur, Mehmet (My University, 2025)
Aim: Hormone receptor (HR)-positive, human epidermal growth factor 2 (HER2)-negative breast cancer which represents the most common subgroup of metastatic breast cancer (MBC). Recently, further subclassification for HER2-negative tumors has emerged as HER2-low. There is limited knowledge regarding the effect of HER2-low expression on outcomes of patients with HR-positive and HER2-negative MBC treated with CDK 4/6 inhibitors plus hormonal therapy. Therefore, we evaluated survival parameters according to HER2-low status for this patient group in this study. Material and Methods: As the Turkish Oncology Group (TOG) Project, retrospectively collected data from 423 patients with HR-positive/HER2-negative MBC treated with ribociclib and palbociclib plus letrozole therapy was assessed. Included patients had metastatic first-line therapy and endocrine-sensitive disease. Survival outcomes were compared between HER2-negative and HER2-low patient groups. Conclusion: HER2-low status had no statistically significant impact on survival in patients treated with palbociclib or ribociclib plus letrozole.
Keywords: Palbociclib; Cyclin-dependent kinase 4/6 inhibitors; HER2-low; ribociclib; hormone receptor positive and HER2 negative advanced breast cancer